A opinião do Estado de S. Paulo nos impeachments dos presidentes Fernando Collor de Mello e Dilma Rousseff - Cauduro, Douglas Hinterholz (2018)
The present study describes and analyses the Estado de S. Paulo’s positioning on Fernando Collor de Mello, in 1992, and Dilma Rousseff, in 2016, impeachment process through its editorial. Altogether, there were studied 10 editorials in 1992; 2 in September, one in October, four in November and three in December. Already in 2016, 11 editorial were analyzed; three in April, four in May, one in June, one in July and two on August. This study uses content analysis to unravel two troubled moments of Brazilian political life through one of the largest newspapers in the country point of view. At the end, it is possible to conclude that are differences in the way both cases were treated. On President Fernando Collor de Mello’s impeachment, the publication regrets the end of the former president government while on President Dilma Rousseff’s impeachment they bet the country will be better without it.